Spatial Analysis of Morphometrics Characteristics of Bastora Basin - Tahseen Abdulrahem Azeez; Shatan Abdullah Muhammad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The aim of the study is to analyze the Morphometric characteristics of discharge Bastora,represented characteristics cadastral,Formal,topographic,and characteristics of the water drainage network, study relied on( GIS)and digital elevation model( DEM) as a tool to set up a network rivers draining map and classified according to the way Strahler to mortabha river basin and draw some morphometric characteristics .the study has revealed the importance of spatial data lind metadadt and its role in morphometric studies and characteristics of the analysis.